PENGARUH TEKANAN WAKTU, MATERIALITAS, DAN RISIKO AUDIT TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Sifa Fauzia (2017)
This study was conducted to examine the effect of time pressure, materiality, and audit risk to premature sign off audit procedure. The population of this study are auditors who work at KAP Jakarta selatan with 6 KAP branches, the are 46 auditors become the sample of this study.the data werw examined using the test of validity and reliability, classical assumption, normality, multicolinearity, and heteroscedastisity. The hypothesis was analysed using the multiple regression analysis with SPSS 20. The result of study showed that time pressuret, materiality and risk audit variabel do not have effect on the premature sign off of procedure audit.